Study of evoked potentials and early development in premature infants - Min, Kyeongil; Jeong, Minjae; Kim, Du Hwan; Lee, Byung Chan; Lee, Eun Sun; Shin, Hyun Iee (Frontiers in Pediatrics, 2025)
IntroductionEvoked potentials have been suggested as potential biomarkers for predicting neurodevelopment. This study aimed to investigate the relationship between evoked potentials (EP) and neurodevelopmental outcomes in preterm infants.MethodsPremature infants admitted to the neonatal intensive care unit of a tertiary referral hospital between March 2020 and March 2023 were included in the study. Among them, only those with EP at a corrected age of 40 weeks were included, meanwhile, infants who did not undergo the test or had abnormal results were excluded. Additionally, patients with follow-up developmental outcomes such as the Hammersmith Infant Neurological Examination (HINE) at 3 months corrected age or the Gross Motor Function Measure (GMFM) at 6 months corrected age were included.ResultsA total of 24 participants were included in this study. No significant differences in the clinical factors and results of the EP studies were observed between the two groups divided by a HINE score of 60. Hierarchical logistic regression analysis revealed that visual EP was the only factor that correlated with the lying and rolling domains of the GMFM (P = 0.028).DiscussionA significant association was observed between the GMFM and visual EP. Integrating the visual EP latency with other parameters may improve clinical assessments to predict developmental outcomes, possibly improving the accuracy of medical interventions and patient outcomes.